Pelaksanaan Collaborative Governance di Desa Budaya Brosot, Galur, Kulonprogo, DI. Yogyakarta - Sambodo, Giat Tri; Pribadi, Ulung (Journal of Governance and Public Policy, 2016)
The paper has the title of the implementation of collaborative governance in the Brosot cultural village, Galur subdistrict,Kulonprogo Regency. Research aimed to know Bagaimana Collborative Brosot cultural village implementation,Galur subdistrict, Kulonprogo Regency and factors any prejudical Collborative Brosot cultural village, Galur subdistrict,Kulonprogo. Regency Research conducted with kualititatif method, withdrawal data done through interview informationsources, observation, and study documentation. Result Research show that, Model Collaborative Governance inDesa Budaya Brosot, generally speaking is equal Model Collaborative Governance that made by Ansel and Gash. Thereis some factor culture affect that Collaborative Governance implementation in Brosot cultural village, namely: kinshiprelation, Arisan, Jam Karet, Musyawarah Mufakat, Nggih Kepanggih ra Ngaruhke, Gotong Royong and Swadaya, Mokogi,Ngombyongi, and Mosobodoa, paternalistic and the People about that is all.